ANALISIS TAX PLANNING UNTUK EFISIENSI PPH BADAN PADA PT. SURYA KENCANA KERAMINDO - Universitas IBA, Hadli; Agustin, Amalia; Amah, Mas (Jurnal Manajemen, 2021)
Abstract: Purpose of this writing thesis a tax planning application see whatcan be done streamline income tax payments at PT. Surya Kencana Keramindo. Method‟s used are writing descriptions method is callecting, sort data obtained interpreted and analyzed so then able to provide completed information for problem‟s breakers. Results of this research expected able to provide information and feedback a PT. Surya Kencana Keramindo can do so as tax planning efficient efforts to achieve profits tax planning to the fullest, but still in frame‟s tax planning. Research conclusion the of this the applications is made corporate tax planning to streamline income tax payble at PT. Surya KencanaKeramindo.